The essence and specificity of subjects socio-communicative interaction in the context of network structures development - Bankouskaya, Yuliya L. (Journal of the Belarusian State University. Sociology, 2020)
The purpose of the article is to identify the qualitative and specific characteristics of subjects social and communicative network interaction. The methodology of the study is synergetics, because communication in the network is a self-supporting and self-organizing open system. Network communication is considered in the article as a multi-channel, intertextual, nonlinear way of organizing the interaction between actors, each of which has its own, independent of network structural elements, links, the presence of many ways of moving information. Consequently, networks create a universal opportunity for communication between representatives of different social strata, leveling their status and role differences. The specifics of the network set the union of its components such as the position of the actors, their relationship, interaction based on available resources. The results of the study can be used as a way to optimize the interaction of actors and the formation of a constructive network dialogue between them.
Keywords: network structures; social communication; interaction; networks; actor